Identity-Based Signature Schemes for Multivariate Public Key Cryptosystems. (5th March 2019) - Chen, Jiahui; Ling, Jie; Ning, Jianting; Ding, Jintai
Abstract: In this paper, we proposed an idea to construct a general multivariate public key cryptographic (MPKC) scheme based on a user's identity. In our construction, each user is distributed a unique identity by the key distribution center (KDC) and we use this key to generate user's private keys. Thereafter, we use these private keys to produce the corresponding public key. This method can make key generating process easier so that the public key will reduce from dozens of Kilobyte to several bits. We then use our general scheme to construct practical identity-based signature schemes named ID-UOV and ID-Rainbow based on two well-known and promising MPKC signature schemes, respectively. Finally, we present the security analysis and give experiments for all of our proposed schemes and the baseline schemes. Comparison shows that our schemes are both efficient and practical.